Exploring the Polar Atmosphere with SCIAMACHY - Gottwald, Manfred; Krieg, Eckhart; Lichtenberg, Günter; von Savigny, Christian; Noel, Stefan; Reichl, Philipp; Richter, Andreas; Bovensmann, Heinrich; Robert, Charles; Weber, Mark; Burrows, John P. (2008)
The German-Dutch-Belgian instrument SCIAMACHY (Scanning Imaging Absorption Spectrometer for Atmospheric Chartography) onboard the European ENVISAT mission provides unique capabilities for exploring atmospheric geophysical parameters. Its design permits continuous measurements from the ultraviolet to the shortwave infrared range exploiting a variety of viewing geometries, including nadir, limb and solar and lunar occultations. Since its launch in early 2002 SCIAMACHY has operated successfully in orbit. ENVISAT’s high inclination orbit carries SCIAMACHY each day 14 times over the arctic and antarctic region. SCIAMACHY has monitored the status of the polar atmosphere in the past 6 years from the bottom (troposphere) up to its top (mesosphere). Reported highlights include BrO plumes in arctic spring, OClO densities and associated ozone hole episodes since 2002. Related to the ozone hole are observations of enhanced Polar Stratospheric Cloud (PSC) occurrence. In the mesosphere we provide a 6 year climatology of Noctilucent Cloud (NLC) rates and sizes together with the existence of a 27-day solar signature in NLC properties. Since the polar atmosphere is considered to be highly sensitive to anthropogenic impacts on the Earth system, and thus to climate change, our record of polar geophysical parameters contributes to the understanding of our changing environment.